1996
DOI: 10.3109/03091909609032524
|View full text |Cite
|
Sign up to set email alerts
|

ECG response of the human body subjected to vibrations

Abstract: In this paper, the ECG response of the human body subjected to vibrations is investigated. Measurements relied on recording the ECG and then computing the normalized difference of the ECG power spectrum density. Ten subjects aged 20-22 years old were exposed for 15 min to vertical vibrations in the frequency range 5-30 Hz. Results show either depression or elevation of the ST segment indicating heart muscle fatigue. The power spectrum density normalized difference also shows that the maximum difference takes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…We believe that the increased amplitude in the R-wave may be due to cardiac muscle fatigue. This is due to the fatigue caused by vibrations as has been reported by the authors [26]. It is well known that …”
Section: W Qasem Et Af Effects Of Vibrations On the Ecgmentioning
confidence: 80%
See 2 more Smart Citations
“…We believe that the increased amplitude in the R-wave may be due to cardiac muscle fatigue. This is due to the fatigue caused by vibrations as has been reported by the authors [26]. It is well known that …”
Section: W Qasem Et Af Effects Of Vibrations On the Ecgmentioning
confidence: 80%
“…The seat consists of a permanent magnet exciter driven by a standard function generator. In all experiments, the vibration frequency was chosen to be at 8 Hz as our earlier findings found that this frequency represents the resonant frequency of the heart [26]. To investigate the effect of the vibration force, two amplitudes were chosen, 3 and 5 mm (peak to peak).…”
Section: Experimental Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors noted a significant effect of body position (supine vs side lying) related to the 2 parameters tested for the primary hypothesis; however, neither contact area nor pressure ratio indicated a significant effect due to HOB angle: 46 Figure 2]). The authors note that the apparently large deviations are due to the high variability between subjects; however, by including subject ID as a cofactor in the analysis, these intersubject differences are accounted for, and the hypothesis test reflects only those effects due to change in position or angle.…”
Section: Primary Objective Measuresmentioning
confidence: 93%
“…15 Available studies on the responses of the autonomic nervous system to occupational WBV have generally indicated degrees of dysfunction and autonomic imbalance. [16][17][18][19] Harstela and Piirainen noted that exposure to WBV may have a significant effect on decreasing heart rate variability; this can be more significant when the subject is under mental stress. 16 Jiao, et al, reported that WBV might significantly activate the sympathetic and suppress the parasympathetic nervous system leading to increased LF/HF ratio.…”
Section: Introductionmentioning
confidence: 99%